Dynamic Response of a Road Bridge Subjected to Passing a Heavy Vehicle over a Standard Irregularity - Numerical Modelling and Experimental Testing - Milan Moravčík (Communications - Scientific letters of the University of Zilina, 2022)
The paper presents an analysis of an actual problem related to dynamic effects to road bridges due to travelling a heavy vehicle over the bridge. Numerical simulations of the dynamic response are applied on a fictitious simple beam of the length Lb = 52 m with an artificial irregularity at midspan, corresponding to a characteristic span L (b5) = 52 m of the ten-span continuous box girder bridge. A heavy four-axle truck m v = 32 t is used for dynamic excitation, travelling over the bridge at passing speed of 70km / h. The obtained results are compared to results of the experimentally tested ten-span continuous pre-stressed reinforced concrete girder bridge at the same speed.